THE INDEPENDENCE OF THE INFORMATION COMMISSION AS A QUASI-JUDICIAL INSTITUTION IN THE INDONESIAN STATE CONSTITUTION - Mizan Malik S; Arief Budiono; Nunik Nurhayati; Nuria Siswi Enggarani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Information Commission plays a strategic role in ensuring the implementation of the right to public information while exercising quasi-judicial authority to resolve public information disputes through mediation and non-litigation adjudication. Despite being legally recognized as an independent institution under Law Number 14 of 2008 concerning Public Information Disclosure, questions remain regarding the extent of its institutional independence within Indonesia's constitutional system. This study aims to analyze the independence of the Information Commission as a quasi-judicial institution and to identify the legal and institutional challenges affecting its impartiality. The research employs a normative juridical method using statutory, conceptual, and doctrinal approaches by examining constitutional provisions, legislation, legal doctrines, and relevant literature. The findings indicate that although the Information Commission possesses adjudicative authority requiring impartiality and independence, its institutional autonomy has not been fully realized due to administrative and secretarial dependence on the executive, potential conflicts of interest, and governance arrangements that may undermine public confidence. These conditions weaken the effective implementation of its quasi-judicial functions. The study concludes that strengthening the Information Commission's independence requires not only regulatory reform but also improvements in institutional governance, organizational capacity, accountability mechanisms, and administrative autonomy. Such reforms are essential to reinforce legal certainty, safeguard objective dispute resolution, and enhance public trust in the constitutional protection of the right to information.